Screening of premalignant and malignant lesions of cervix by visual inspection with (acetic acid or Lugol’s iodine) and PAP smear - Mahezabeen; Thobbi, Vidya A. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Cervical cancer is the primary cause of morbidity and fatality globally among women. It is essential to unfold a screening test with high sensitivity and specificity. This study compared the effectiveness of visual inspection of the cervix with acetic acid (VIA) and lugol’s iodine (VILI) versus the Pap smear in detecting cervix cancer. Methods: In this prospective diagnostic validation study, 1000 patients were included and screened for cervix cancer using VIA, VILI and pap smear. The outcomes were obtained, contrasted, and statistically analysed. Results: Among enrolled patients, 17.8% had a positive PAP smear, 43.2% had a positive VIA/VILI, and 14.0% had a positive COLPO. The patients’ biopsies revealed that 7.6% had chronic cervicitis, and 5.9% had cervical intraepithelial neoplasia (CIN1). The sensitivity was 87.64% for VIA/VILI and PAP smear, whereas the specificity was only 66.4%. PAP smear and biopsy had a sensitivity of 37.58% but a specificity of 85.43%. The sensitivity of VIA/VILI and biopsy was 89.93%, whereas the specificity was 64.98%. Conclusions: The current investigation showed that VIA/VILI is more sensitive than PAP.